Optimizing and using AI to study of the cross-section of finned tubes for nanofluid-conveying in solar panel cooling with phase change materials - Zhu, Chaoyang (Engineering analysis with boundary elements, 2023)
This study numerically investigated the effect of applying different shapes of nanofluid-conveying pipes on a thermal solar panel system. Two pipes with circular, elliptical, and square shapes were employed in this system. Likewise, paraffin wax Phase Change Material (PCM) was used in the solar thermal panel. A large number of spherical pin fins were installed over the pipes inside the PCM. The two phases of the NF were simulated, and all equations were solved using an element-free Galerkin method based on weak form. The results showed that the elliptical pipes increased the volume of the liquid PCM around them, while the circular pipes raised the quantity of solid PCM around them. That is to say, these two pipe types brought about the maximum difference in the volume of the phase change material (5%). When t = 2000 s, the temperature could decrease by >1% through circular rather than elliptical pipes. In the same period, the heat transfer rate of the circular pipes was 16.17% above that of elliptical pipes, whose heat transfer was 48.43% higher compared to the square pipes. When the solar panel was hot, elliptical pipes maximized the temperature of the output NF, and circular pipes minimized the NF's temperature at the outlet.